Developing a trust model using graph and ranking trust of social messaging system - Mostafa Heidarzadeh Kalahroudy; Kheirollah Rahsepar Fard; Yaghoob Farjami (International Journal of Electrical and Computer Engineering (IJECE), 2023)
Trust is an important issue in social interactions, especially in using cyberspace services. In this paper, a trust and evaluation model are proposed based on which the government can provide reliable services to users. The model is a distributed and hierarchical model. First, the number 12 trust criteria and the weight of these criteria were extracted using the analytical hierarchy process (AHP) and analytic network process (ANP) techniques. Second, to obtain the trust in the service examined, for each criterion, a graph of trusted entities is proposed. Then, a weighted graph with the number of trusted entities called trust pathways measure will be obtained. To test the model, the effect of the 12 criteria on three important evaluation factors over seven widely used social services was rated by three experts. The trust of each service was obtained, which was satisfactory as compared to a valid organizational evaluation. Finally, the correlation coefficient of this comparison was 70.37%, indicating that the results from this model were appropriate.